Nitrogen/sulfur co-doped graphene networks uniformly coupled N-Fe2O3 nanoparticles achieving enhanced supercapacitor performance. (10th March 2018) - Wang, Ying; Zhang, Mingmei; Pan, Denghui; Li, Yuan; Ma, Tianjiao; Xie, Jimin
Abstract: Nitrogen/sulfur dual-doped graphene with uniformly coupled N doped Fe2 O3 (N-Fe2 O3 /NSG) composite has been successfully synthesized via an easily one-step green method, in which ammonium thiocyanate (NH4 SCN) is applied as nitrogen source and sulfur source without adding other alkali sources or dispersants. Surprisingly, N atom is doped into Fe2 O3 while being doped into graphene in hydrothermal process. XPS reveals that the N atom percentage in N-Fe2 O3 /NSG is 2.75% higher than that in NSG (1.69%) at the same condition, indicating that N is successfully doped into Fe2 O3 . To the best of our knowledge, the N-Fe2 O3 /NSG composite is applied to supercapacitor electrode material for the first time and the superior electrochemical properties has been proved. In 6.0 M KOH electrolyte, N-Fe2 O3 /NSG electrode exhibit large specific capacitance (1567 F g −1 at 1 A g −1 ) and a high rate capability (864 F g −1 even at 10 A g −1 ). Particularly, the specific capacitance remains at 91.3% of the initial value after 5000 cycles under the current density of 5 A g −1 . This pronounced supercapacitor performance is attributed to the incorporation of N and S into the graphene network to introduce more defects in the graphene lattice structure, activating the associated C atoms and effectively reducing the activation energy required for oxidation-reduction reactions of graphene surface and also the increased active point of Fe2O3 due to nitrogen doping. Graphical abstract: N-Fe2 O3 /NSG composite has been successfully synthesized by an easily one-step hydrothermal method, in which N-Fe2 O3 particles with 20–30 nm in size uniformly anchored on the surface of NSG sheet, and exhibits excellent charge/discharge stability and long-term cycling life (91.3% of capacitance retention after 5000 cycles). Image 1